PENGARUH KUALITAS LAYANAN ELEKTRONIK, PERSEPSI MANFAAT, DAN PERSEPSI NILAI TERHADAP MINAT PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Marketplace Lazada di Wilayah Pekalongan) - Inayah, Risqi Rahma; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Lazada is an e-commerce platform that has been operating in Indonesia since 2012. Lazada has seen a decline in brand perception and website visitors over the last five years, from 2018 to 2022. This decline is accompanied by a surge in customer complaints. Amidst intense competition with competitors, Lazada needs to improve the quality of its electronic services and provide maximum perceived usefulness and value to its customers. This study focuses on Lazada's marketplace consumers in Pekalongan City/Regency who made two or more transactions on Lazada between 2022 and 2023. Using a quantitative approach with a sample of 117 respondents, data was collected via a questionnaire and analyzed with Structural Equation Model (SEM) using AMOS version 24. Results reveal positive connections between e-service quality, perceived usefulness, and perceived value with customer satisfaction. Furthermore, perceived value and customer satisfaction are linked to repurchase intention. However, a negative relationship is found between e-service quality, perceived usefulness, and repurchase intention.